Analysis on Blood Transfusion Service System According to GMP (A Case Study in Blood Transfusion Unit of Indonesian Red Cross (UTD PMI) of Polewali Mandar) - A. Emy Purnama (Universitas Muhammadiyah Yogyakarta, 2018)
Good Manufacturing Practice (GMP) is an absolutely thing which has to do in every units of blood providers to eliminate the risks in the quality of Blood Providing Unit under the control of BPOM. The purposes of this research are; to get the information in budgeting aspect and government regulation; quality and personnel management; buildings, facilities and equipment; and the documentations of giving blood transfusion service according to GMP in UTD PMI of Polewali Mandar. The research method is qualitative based on the case study. UTD PMI of Polewali Mandar has not applied this as well as the others yet. Because of the government’s regulation has not inclined yet. UTD PMI of Polewali Mandar is not consistent yet with GMP because of the low quality of the human resources. The buildings, facilities and equipment are not in compliance with GMP standard. The documentation is simple, it is incomplete and no commitment yet to make it runs. To overcome those obstacles, the comprehensive strategies are needed; such as government should publish the government regulation to support the blood services according to GMP and the commitment from the other parties to run it properly.